2008
DOI: 10.1590/s0037-86822008000500007
|View full text |Cite
|
Sign up to set email alerts
|

Pseudomonas aeruginosa: disseminação de resistência antimicrobiana em efluente hospitalar e água superficial

Abstract: Revista da Sociedade Brasileira de Medicina Tropical 41(5):470-473, set-out, 2008 ARTIGO/ARTICLEAntibióticos e bactérias resistentes são descartados em grandes quantidades no ambiente 6 como resultado do aumento e freqüente uso indiscriminado de antibióticos nas práticas médicas, veterinárias e agrárias. As águas dos rios são os principais receptores desses poluentes, uma vez que recebem os esgotos urbano, industrial e hospitalar. Os rios são considerados uma das principais fontes de água, direta ou indiretame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
1
9

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 11 publications
0
8
1
9
Order By: Relevance
“…in aquatic environments did not note the presence of P. putida in your samples (Suzuki et al 2013;Fuentefria et al 2008). However, the present study found two P. putida isolates in Água Boa stream water that showed resistance to at least one antibiotic.…”
Section: Resistance Profilescontrasting
confidence: 79%
See 1 more Smart Citation
“…in aquatic environments did not note the presence of P. putida in your samples (Suzuki et al 2013;Fuentefria et al 2008). However, the present study found two P. putida isolates in Água Boa stream water that showed resistance to at least one antibiotic.…”
Section: Resistance Profilescontrasting
confidence: 79%
“…isolated, three (23 %) showed resistance to the tested antibiotics (Table 4): one species of P. aeruginosa was resistant to Imipenem, Meropenem, Piperacillin/Tazobactam, Cefepime, and Ceftazidime; one species of P. putida had intrinsic resistance to Piperacillin/Tazobactam; and one strain of P. putida had Cefepime and Gentamicin resistance. Fuentefria et al (2008) found that 31 % of P. aeruginosa isolates from surface water also showed resistance to imipenem or meropenem.…”
Section: Resistance Profilesmentioning
confidence: 99%
“…P. pseudoalcaligenes, the most common species found, is often isolated from environmental samples and has also been also related to antibiotic resistance (Quinteira et al 2005). Resistant P. aeruginosa have been commonly found in hospital effluents (Fonseca et al 2005;Fuentefria et al 2008;Tuméo et al 2008;Yang et al 2009;Fuentefria et al 2011). It is important to consider the presence of resistant isolates from other Pseudomonas species, since they may represent a possible reservoir of resistance determinants in the hospital effluent, as shown by Koh et al (2004).…”
Section: Discussionmentioning
confidence: 99%
“…The S. aureus is among the most frequent nosocomial pathogens, as the resistance to multiple drugs is common and contributes to the difficulty in the treatment of infections [17]- [19].…”
Section: Introductionmentioning
confidence: 99%